ANALISIS TUMBUH DUA VARIETAS TERUNG (Solanum melongena L.) PADA PERBEDAAN JENIS PUPUK ORGANIK CAIR (Growth Analysis of Two Eggplant (Solanum melongena L.) Varieties on Different Types of Liquid Organic Fertilizer) - Made Deviani Duaja; . Arzita; Pasro Simanjuntak (Bioplantae, 2013)
The aim of this research were to determine the best combination between varieties and the types of organic liquid fertilizers. This research was conducted at the Teaching and Research Farm Faculty of Agriculture, University of Jambi. The laboratory analysis for liquid organic fertilizer was done ​​in BIOTROP, Bogor. This research used Completely Randomized design (CRD) with four combination treatments between variety and types liquid organic fertilizer. The treatments were Mustang Variety and organic liquid fertilizers Alam Natural, Mustang Variety and organic liquid fertilizers Golden Harvest, Hijo Variety and organic liquid fertilizers Alam Natural, Hijo Variety and organic liquid fertilizers Golden Harvest. The result showed that Hijo variety and Alam Natural liquid organic fertilizer trend gave the highest Leaf Area Duration (DLD), Net Assimilation Rate (NAR), Relative Growth Rate ( RGR), Keywords: Liquid,organic, fertilizer eggplant.